2006
DOI: 10.1007/s00198-006-0219-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency and the blunted PTH response in established osteoporosis: the role of magnesium deficiency

Abstract: Due to errors on the part of the typesetter, the article was published with incorrect versions of the column heads of Table 1 and the illustration and legend of Fig. 2. The correct table and figure are given in full here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 0 publications
1
49
1
4
Order By: Relevance
“…We were surprised to find that PTH(i) levels remained unchanged in our subjects. Hypomagnesemia blunts the PTH(i) response and might be one possible explanation for our finding [37]. Adewoye and coworkers have reported that patients with sickle cell anemia have low red cell and plasma magnesium levels [38,39].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We were surprised to find that PTH(i) levels remained unchanged in our subjects. Hypomagnesemia blunts the PTH(i) response and might be one possible explanation for our finding [37]. Adewoye and coworkers have reported that patients with sickle cell anemia have low red cell and plasma magnesium levels [38,39].…”
Section: Discussionmentioning
confidence: 75%
“…Adewoye and coworkers have reported that patients with sickle cell anemia have low red cell and plasma magnesium levels [38,39]. Clinical trials with magnesium loading might be required to evaluate this potential mechanism in SCD [37].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in vitamin D consumption and status may have also contributed. In adults with established osteoporosis, magnesium deficiency has been shown to blunt PTH response [20]. Although serum levels of this cation were not measured in the current study, this possibility is an important consideration in a malnourished group with AN.…”
Section: Discussionmentioning
confidence: 79%
“…It should be noted that the relation between the concentrations of PTH and the concentrations of 25VTD is probably dependant on the magnesium status of the subjects tested. Indeed, a relative hypomagnesemia is able to explain why PTH does not rise, even if the patient is clearly vitamin D insufficient (25).…”
Section: Vitamin D Deficiency and ''Desirable'' Serum Valuesmentioning
confidence: 99%